Improving small farmer food and fruit crop production - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
The document emphasizes the specific objective of the IICA proyect which deals with improvements in the production and productivity of small food and fruit crop farmers by increasing the quantity and quality of inputs and services available to them. The main objective is to improve their standard of living by increasing income and reducing the drudgery of their work. The project strategy is characterised by the collaboration of three major institutions: IICA, the Ministry of Agriculture and the Ministry of Regional Development in tackling the problem of production and productivity on the analysis, technology transfer, institutional support and proyect development assistance fronts.